The kid who would be king [videorecording (DVD)] - Cornish, Joe, 1968-; Serkis, Louis Ashbourne, 2004-; Taylor, Tom, 2001-; Chaumoo, Dean; Dorris, Rhianna (Twentieth Century Fox Home Entertainment, 2019)
Alex is just another nobody at school, picked on by bullies and struggling to get through the day. But all that changes when he finds a sword that turns out to be King Arthur's legendary weapon, Excalibur. Unfortunately for Alex, the sword also comes with an enemy -- the sinister Morgana, who has plans to conquer Britain. Alex's only chance is to assemble a new Round Table to fight Morgana and save the world.